The Role of Green Chemistry in Achieving Sustainable Development (Development Engineering Conferences Center Articles Database, 2026)
Green chemistry has emerged as an essential approach to address growing environmental, approach to address growing environmental, economic, and social challenges caused by conventional chemical processes. By focusing on the design of safer chemicals and environmentally friendly processes, green chemistry plays a significant role in promoting sustainable development. This review article discusses the fundamental principles of green chemistry and examines its contribution to the environmental, economic, and social dimensions of sustainable development. The findings highlight that the application of green chemistry principles can reduce waste generation, minimize hazardous substances, improve energy efficiency, and enhance human health and environmental protection. Overall, green chemistry is a key pathway toward achieving long-term sustainability.